Economic Crisis and Attitudes Towards Democracy: How Ideology Moderates Reactions to Economic Downturns - Jurado, Ignacio; Navarrete, Rosa M. (Frontiers in Political Science, 2021)
This paper studies the extent to which economic crises bust different reactions depending on individual ideological identity. Our argument is that individual left-right identification shapes how citizens evaluate the functioning of democracy, and consequently, it moderates the impact of economic crises on democratic discontent. We argue that left-wing individuals’ views on democratic performance would be more heavily affected by economic results and strongly shaped by the (in)capacity of a democracy to represent its citizens in its reaction to the economic crisis. After testing our argument with data from the ESS, we provide evidence from a survey experiment conducted in Spain. Both analyses show that economic crises are relevant in explaining democratic dissatisfaction, but the strength of their impact depends on ideological identities. Economic results have a stronger effect on the satisfaction with democracy of left-wing individuals by negatively affecting their perception of the functioning of democratic representation.